Application of SBA-Pr-SO3H in the synthesis of benzoxazole derivatives - Ziarani, Ghodsi Mohammadi; Badiei, Alireza; Nahad, Monireh Shakiba; Hassanzadeh, Malihe (European Journal of Chemistry, 2012)
Propylsulfonic acid functionalized SBA-15 (SBA-Pr-SO3H) catalyzed the synthesis of 2-aryl benzoxazoles from 2-aminophenol and benzoyl chloride derivatives in good yields under reflux condition in acetic acid. In solvent free condition, hydroxybenzanilide derivatives were obtained.